Reading the Background: The Textual and the Visual in Steve Tomasula’s The Book of Portraiture - Pawel Frelik (Sillages Critiques)
Steve Tomasula’s VAS: An Opera In Flatland (2002) has been hailed as one of the most innovative literary works combining text and image in a seamless whole. The Book of Portraiture, the author’s 2006 novel, at first appears to be a much more humble affair in this respect. Its central preoccupation with titular portraits, or images of humanity in general, and the universal impulse to picture ourselves in paint, dreams, photography, electronic data and genetic code is first and foremost deployed in a series of interlocked and highly complex narrative chapters. While the images (for example motifs from the sketches by Velasquez, who is the protagonist of one of the chapters, or pixelated nudes culled from Internet websites) are used throughout, they seem to constitute an underexposed background to the central verbal story of image and imaging. The article demonstrates how these graphic elements of The Book of Portraiture, which include not only the images mentioned above but also elements of textual layout, coloring and framing of pages, do, in fact, function as an integral part of Tomasula’s project, whose recurrence and distribution are not merely ornamental or decorative. Instead, they constitute an important layer of the narrative, whose significance can only be glimpsed when the reader has re-focused their attention from the textual foreground to the visual background.